50.8k views
6 votes
Help me plzzzzzzzzzzzzzz

Help me plzzzzzzzzzzzzzz-example-1
User Reilly
by
4.6k points

2 Answers

6 votes
f(x) = -3x^2 - 6x, Find f(-9)

Substitute -9 for every x.

-3(-9)^2 - 6(-9)

Multiply and get final value.

-243 - 6(-9)

-243 + 54

Answer: -189
User Darren Griffith
by
4.9k points
3 votes

Answer:

f(-9) = -189

Explanation:

f(x) = -3x² - 6x

Plug in -9 for x.

f(-9) = -3(-9)² - 6(-9)

According to PEMDAS (parentheses/exponents | multiplication/division | addition/ subtraction), we should solve the exponents first.

f(-9) = -3(81) - 6(-9)

Now, multiply.

f(-9) = -243 + 54

Now, add.

f(-9) = -189

This is your answer.

Hope this helps!

User Marten
by
4.3k points